Improving Writing Ability Through Media Story Images Of The Eight Grade Students Private SD HKBP Pematangsiantar In Academic Year 2018/2019: Improving Writing Ability Through Media Story Images Of The Eight Grade Students Private SD HKBP Pematangsiantar In Academic Year 2018/2019 - Jumaria Sirait (Jurnal Mantik, 2020)
The aims of this study is to improve students' writing abilities in elementary schools. Learning media picture story is one of the Efforts made in the learning process to improve the writing ability of elementary students. This picture is more media story Strategically applied Because it can inspire students 'reasoning power, so that students' creative ideas emerge, and Ultimately they are Able to write. This is in line with the purpose of the study, the which is to find out the level of writing ability through the medium of the picture stories of VI grade students of Pematangsiantar Private Elementary School in 2018/2019. The research Carried out is classified as a class action research (research actions) conducted by the teacher for the purpose of optimizing student learning outcomes Also while increasing the professional competence of teachers According to the topic under study. The topic studied was related to the ability to write based on the use of instructional media items, namely picture stories. The research respondents were grade VI elementary school students, with the application of the pre-test and post-test. Before learning is done, students' ability to write is still low, after learning with the application of media images the ability of students has Increased. In the first cycle, the pre-test results of students' writing abilities were 16:12%, and the post-test results Reached 25.80%. In the second cycle, the results Obtained by students in writing Reached 43. 93%, and in cycle III the results Achieved by students Became 70.96%. Barriers experienced by teachers and students are learning unpreparedness in changing situations and minimal practice time.